Validation of the effector profile of Phytophthora betacei (2017)
Phytophthora betacei is a new species that was determined through a set of genetic, ecologic and morphological characteristics that make it stand it apart independently from P. infestans. This new species is capable of infecting tree tomato (Solanum betaceum) yet it is not able to infect common potato species. The effector proteins determine this host-pathogen interaction, RXLR and Crinkler effectors are the most studied in the Phytophthora genus for its degree of conserved regions. A bioinformatic study did predictions of new effectors based on the sequenced fragments of samples of the infecting agent that caused an outbreak in Pasto, Colombia. The objective of this study was to validate some of this predictions and contribute to the genetic profile of this new species. There were two gene candidates that are potentially unique genes for P. betacei. Finally, Pex151803 was validated experimentally as an effector gene